2009
DOI: 10.1097/ccm.0b013e318192fbd7
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and functional outcome correlates of brain tissue hypoxia in traumatic brain injury*

Abstract: Hypoxic episodes are common after severe TBI, and most are independent of ICP elevations. Most episodes of hypoxia occur while cerebral perfusion pressure and mean arterial pressure are within the accepted target range. There is no clear association between PaCO2 and hemoglobin with BTpO2. The young age and high prevalence of traumatic subarachnoid hemorrhage in this cohort may limit its generalizability. Increased frequency of hypoxic episodes is associated with poor functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(90 citation statements)
references
References 37 publications
1
84
1
4
Order By: Relevance
“…Adequate function of mitochondria is pivotal for the survival and activity of all brain cells, and even brief periods of oxygen or glucose deprivation could shut down brain functions within seconds, damaging neurons within minutes. 4 Abundant data from retrospective studies and prospective clinical trials have shown brain hypoxia to be an early predictor of adverse outcomes after TBI, [5][6][7] because efficient ATP production by the mitochondrial respiratory chain relies on continuous oxygen supply.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…Adequate function of mitochondria is pivotal for the survival and activity of all brain cells, and even brief periods of oxygen or glucose deprivation could shut down brain functions within seconds, damaging neurons within minutes. 4 Abundant data from retrospective studies and prospective clinical trials have shown brain hypoxia to be an early predictor of adverse outcomes after TBI, [5][6][7] because efficient ATP production by the mitochondrial respiratory chain relies on continuous oxygen supply.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…16 Common causes of elevated ICP include development of mass lesions such as subdural hematoma, epidural hematoma, and intracerebral contusions. Additionally, cerebral edema and communicating and noncommunicating hydrocephalus are treatable causes of increased ICP.…”
Section: Physiology Of Icp and Cppmentioning
confidence: 99%
“…The correlation between clinical deterioration and ICP is not a robust one: because the brain is anatomically compartmentalized, fatal herniation syndromes may occur without associated changes in ICP, for example, after posterior fossa hemorrhage or infarction. Studies conducted in TBI patients with parenchymal oxygen or microdialysis probes demonstrate that brain tissue hypoxia and metabolic distress can occur independently of ICP or CPP [9,10], perhaps superseding the latter in terms of prognostic significance [11]. Evidence that cerebral pressure autoregulation is globally or regionally impaired following severe TBI means that ischemia can occur at apparently adequate CPP levels [12,13]-a serious challenge to the current recommendation of a single CPP target in all patients [14].…”
mentioning
confidence: 99%